MODEL PERHITUNGAN UNIT COST LAYANAN KESEHATAN DENGAN METODE BIAYA KONVENSIONAL DAN ABC (STUDI KASUS DI PUSKESMAS â€œXâ€ KABUPATEN LUMAJANG) - Mulyono, Imam (Jurnal Analisa Akuntansi dan Perpajakan, 2017)
@font-face { font-family: "Times New Roman"; }@font-face { font-family: "宋体"; }@font-face { font-family: "SimSun"; }p.MsoNormal { margin: 0pt 0pt 0.0001pt; text-align: center; font-family: "Times New Roman"; }p.MsoFooter { margin: 0pt 0pt 0.0001pt; text-align: center; font-family: "Times New Roman"; }span.msoIns { text-decoration: underline; color: blue; }span.msoDel { text-decoration: line-through; color: red; }div.Section0 { }Public Health Center (PHC) is one organization that is very strategic and have special authority in the health services so that they are entitled to innovate in the health service. Unit cost calculation purposes of research compiled by the PHC Unit Cost Konvensional Method and Activity Based Costing (ABC) Approach. The study was conducted at PHC "X" Lumajang City. The Research Methods used a case study with the source data from interviews and documentation. Results of this study include the calculation model of unit cost with konvensional methods, the classification of the direct costs and indirect costs, acquired unit cost by considering all PHC staff salaries amounted Rp.124.987,00, while if the total salaries of employees of PHC "X" that civil servants are not included in the total cost of the component units of the average unit cost of each service is Rp. 36.087,00. Analysis of calculation models of unit cost of service with the ABC method, classified in activities, among other things -Producting Activities Result, Result-Contribution Activities, Support Activities, and Hygiene & Houskeeping Activities, acquired PHC unit cost with consideration of all PHC staff salaries amounting to Rp. 124,876.00, whereas if the total salaries of employees of PHC "X" that civil servants are not included in the total cost of the components, the unit cost of the service on average for each service, patients bear only Rp. 44.103,00.